2021
DOI: 10.1101/2021.08.30.458182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Apelin signaling dependent endocardial protrusions promote cardiac trabeculation in zebrafish

Abstract: During cardiac development, endocardial cells (EdCs) produce growth factors to promote myocardial morphogenesis and growth. In particular, EdCs produce Neuregulin which is required for ventricular cardiomyocytes (CMs) to seed the multicellular ridges known as trabeculae. Defects in Neuregulin signaling, or in endocardial sprouting towards CMs, cause hypotrabeculation. However, the mechanisms underlying endocardial sprouting remain largely unknown. Here, we first show by live imaging in zebrafish embryos th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…It has been recently shown that the angiocrine molecule COL15A1 promotes CM proliferation in mice (Rhee et al, 2021). In zebrafish, the two endothelial compartments; the endocardium and coronaries play a vital role during heart development (Qi et al, 2022;Rasouli and Stainier, 2017) and regeneration (Kikuchi et al, 2011a;Lepilina et al, 2006;Marín-Juez et al, 2019;Münch et al, 2017).…”
Section: Vegfc Is An Angiocrine Required For Cardiac Regeneration Ind...mentioning
confidence: 99%
“…It has been recently shown that the angiocrine molecule COL15A1 promotes CM proliferation in mice (Rhee et al, 2021). In zebrafish, the two endothelial compartments; the endocardium and coronaries play a vital role during heart development (Qi et al, 2022;Rasouli and Stainier, 2017) and regeneration (Kikuchi et al, 2011a;Lepilina et al, 2006;Marín-Juez et al, 2019;Münch et al, 2017).…”
Section: Vegfc Is An Angiocrine Required For Cardiac Regeneration Ind...mentioning
confidence: 99%